Splenic Artery Aneurysm Case Report - Pouya Abhari; Sina Abhari; Anwar Jackson; Ahmed S. Z. Moustafa; Leo Mercer; Mohammad Ashraf (Case Reports in Obstetrics and Gynecology)
Splenic artery aneurysm rupture is a rare complication of pregnancy with very high maternal and fetal mortality rate. In this paper, a case of splenic artery aneurysm rupture at 34 weeks of gestation with both maternal and fetal survival is presented.